Bio-engineered solution in enhancement of septic sludge with artificial immune system - Ting, Sie Chun; Ismail , Amelia Ritahani; Abdul Malik, Marlinda (2012)
In Sarawak, most of the residential properties are connected to septic tank where only toilet wastes are accepted. Overtime, solid retention in the septic tank will be accumulated and result in discharging into the drain hence, polluting our waterways. Therefore, regular desludging is required. The raw sludge will be treated in the Septic Sludge Treatment Plant (SSTP) before the wastewater is being discharged into the waterway. In this paper, the SSTP model will be outlined using Artificial Immune System (AIS) technique called Clonal Selection Algorithm (CSA). AIS is defined as a computational paradigm that is inspired by human immune system. The immune system has the ability to build repertoires of cells and molecules to resist invading disease-causing elements. Therefore, in the engineering perspective, utilizing the ideas of immune systems will be useful as an engineering tool. In this study, CSA inspired by the Clonal Selection theory of immune systems that explains how B and T lymphocytes (cells) improve their response to antigens over time will be used to identify the behaviour of the SSTP. Moreover, the CSA describes that the cells will recognise the antigen proliferation which will be selected against those do not. The effluents namely Chemical Oxygen Demand (COD) and Total Suspended Solids (TSS) are analysed to identify the performance of the SSTP. As such, this approach will allow better forecasting on the function of SSTP and in turn, prevents infringement of future environmental balance.